2020
DOI: 10.34172/ehem.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of phenanthrene-polluted soil using Bacillus kochii AHV-KH14 as a halo-tolerant strain isolated from compost

Abstract: Background: Phenanthrene (PHE) is a polycyclic aromatic hydrocarbon (PAH) with crystalline structure of C14H10, which was produced from incomplete combustion of hydrocarbons and fossil fuels and can cause harmful biological effects. Bioremediation using halophilic bacteria is payed attention over chemical methods due to considerable benefits. Methods: In the present study, a halo-tolerant bacterium Bacillus kochii strain AHV-KH14 was isolated from municipal compost, and used for the bioremediation of PHE from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…By comparing the TPH removal rate (28.1%), it can be concluded that the removal rate observed in the oil-contaminated soils can be attributed to the biodegradation activity of native microorganism (23), which is consistent with the results of some studies (24)(25)(26). Feizi et al investigated the TPH bioremediation in polluted soils using bacteria under conditions approximately similar to the present study, and reported the TPH removal efficiency of 17.7%, which is similar to that reported in the present study (28.1%) (27). Safdari et al in a study on the bioremediation of TPH, reported that the initial concentrations of TPH were reduced by 4.5% in the natural attenuation, which is very lower than that reported in the presented study.…”
Section: Discussionsupporting
confidence: 91%
“…By comparing the TPH removal rate (28.1%), it can be concluded that the removal rate observed in the oil-contaminated soils can be attributed to the biodegradation activity of native microorganism (23), which is consistent with the results of some studies (24)(25)(26). Feizi et al investigated the TPH bioremediation in polluted soils using bacteria under conditions approximately similar to the present study, and reported the TPH removal efficiency of 17.7%, which is similar to that reported in the present study (28.1%) (27). Safdari et al in a study on the bioremediation of TPH, reported that the initial concentrations of TPH were reduced by 4.5% in the natural attenuation, which is very lower than that reported in the presented study.…”
Section: Discussionsupporting
confidence: 91%
“…Bacillus kochii AHV‐KH14 was used for bioremediation of phenanthrene‐polluted soil (Feizi et al . 2020). Di‐(2‐ethylhexyl) phthalate contaminated red soil could be remediate by Gordonia terrae RL‐JC02 (Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…B. kochii has been isolated from some food sources, manufacturing sites (Seiler et al 2012) andsoil (Liu et al 2017). Feizi et al (2020) rst reported that B. kochii isolated from compost had the ability of phenanthrene biodegradation, however, there are not more studies. In our study, B. kochii was rst found that had a high neutral protease activity and co-cultured with B. amyloliquefaciens to promote the FCT sensory quality.…”
Section: Acquisition Of Functional Microorganismsmentioning
confidence: 99%
“…However, More than 3% starch content can have a negative impact on the sensory quality of FCT. Meanwhile, starch degrades into the soluble polysaccharides or reducing sugars which can improve the sweetness and aftertaste of FCT (Feizi et al 2020). The protein content of tobacco should drop to around 5% before the aging process, and excess protein content in FCT may be more irritation and off-avor (Han et al 2010).…”
Section: Introductionmentioning
confidence: 99%